Kleinian groups and hyperbolic 3-manifolds : proceedings of the Warwick Workshop, September 11-14, 2001 - Komori, Yōhei, 1966-; Markovic, V. (Vladimir); Series, Caroline (London Mathematical Society lecture note series, 2003)
Collection of papers summarising the state of the art. Ideal for graduate students or established researchers.